Effect of coordination movement using the PNF pattern underwater on the balance and gait of stroke patients - Jung, Sang-In; Kim, Kyoung; Lee, Dong-Kyu (Journal of Physical Therapy Science, 2015)
[Purpose] To investigate the effect of coordination movement using the Proprioceptive Neuromuscular Facilitation pattern underwater on the balance and gait of stroke patients. [Subjects and Methods] Twenty stroke patients were randomly assigned to an experimental group that performed coordination movement using the Proprioceptive Neuromuscular Facilitation pattern underwater and a control group (n =10 each). Both the groups underwent neurodevelopmental treatment, and the experimental group performed coordination movement using the Proprioceptive neuromuscular facilitation pattern underwater. Balance was measured using the Berg Balance Scale and Functional Reach Test, and gait was measured using the 10-Meter Walk Test and Timed Up and Go Test. To compare in-group data before and after the intervention, paired t-test was used. Independent t-test was used to compare differences in the results of the Berg Balance Scale, Functional Reach Test, 10-Meter Walk Test, and Timed Up and Go Test before and after the intervention between the groups. [Results] Comparison within the groups showed significant differences in the results of the Berg Balance Scale, Functional Reach Test, 10-Meter Walk Test, and Timed Up and Go Test before and after the experimental intervention. On comparison between the groups, there were greater improvements in the scores of the Berg Balance Scale, Functional Reach Test, 10-Meter Walk Test, and Timed Up and Go Test in the experimental group. [Conclusion] The findings demonstrate that coordination movement using the Proprioceptive Neuromuscular Facilitation pattern under water has a significant effect on the balance and gait of stroke patients.